Torsional Vibration Attenuation Characteristics and Stiffness Identification of Flexible Coupling in Vehicle Power Train. (12th November 2020) - Fu, Shengping; Luo, Ning; Huang, Hanlin; Zhou, Yuhang; Ming, Wei
Abstract : Flexible coupling is one of the crucial components for vibration attenuation used in vehicle power train. Vibration attenuation characteristics and stiffness identification of flexible coupling are profoundly studied aiming at one vehicle power train. Firstly, the dynamics model of each crucial transmission component in power train is constructed. And the torsional vibration model of power train is established according to the concentrated mass method. The effects of coupling stiffness on vibration responses of power train are thoroughly analyzed based on system concentrated mass dynamics model. Secondly, the sensitivities of natural frequency and main forced vibration response parameters are calculated. The coupling stiffness is proved to be a sensitive parameter. Finally, taking the Geislinger coupling as an example, the damping and stiffness characteristics are acquired according to the parameter identification method based on the quantity of test data. The results provide the theory basis for the dynamics optimization of power train.